Fishing boats at Harbor Wharf number 2, Fisherman's Wharf, - Albert Walton DeRome:::Creator::::::::::::
Lampara in foreground, small purse seiner in background at dock, at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.) See also photo numbers 1-957 & 1-961.